ASSESSING COGNITIVE AND CREATIVITY COMPETENCES IN PRE-PRIMARY CHILDREN BASED ON LANGUAGE EDUCATION ACHIEVEMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The research examines the assessment of preschool children's cognitive and creative competences based on their linguistic achievement. It highlights that in early childhood education, language skills are closely linked to the development of critical thinking, problem solving and creativity. Although international and national educational documents stress the importance of these skills, there is a lack of clear methodologies for assessing them in the educational process. The study used a quantitative analysis to develop a specific test (a set of tasks) to assess the cognitive and creative competences of children aged 5-6. The tasks of the test focused on the ability to understand and analyse texts, to create stories and to solve linguistic tasks. Data analysis was carried out using IBM SPSS software and Cronbach's Alpha coefficient was calculated to assess the reliability of the test. Descriptive statistics, paired t-tests and Spearman's correlation analysis were used. The results showed that there were no significant differences in cognitive and creative abilities between boys and girls, but there were individual variations in performance. Analytical competences proved to be slightly higher than creative competences, with no statistical significance. Note also that learning skills have a strong correlation with critical thinking skills and problem-solving bears a relationship to cognitive attainment. The research confirmed that language education composes an integral part of developing the child’s cognitive and creative skills. These results can be further implemented in the training process by developing methodical materials of the pre-primary age based on the requirements for effective diagnostics of cognitive and creative abilities in children.